2021
DOI: 10.1016/j.envres.2021.110856
|View full text |Cite
|
Sign up to set email alerts
|

Second versus first wave of COVID-19 deaths: Shifts in age distribution and in nursing home fatalities

Abstract: OBJECTIVE To examine whether the age distribution of COVID-19 deaths and the share of deaths in nursing homes changed in the second versus the first pandemic wave. ELIGIBLE DATA We considered all countries that had at least 4000 COVID-19 deaths occurring as of January 14, 2020, at least 200 COVID-19 deaths occurring in each of the two epidemic wave periods; and which had sufficiently detailed information available on the age distribution of these deaths. We also conside… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 16 publications
8
104
1
1
Order By: Relevance
“…This is in contrast to previous studies from other European countries, which have shown that patients hospitalized during the second wave were relatively younger [ 45 , 46 ]. Despite those age differences among hospitalized patients at different phases of the pandemic, it has been shown that >80% of deaths occurred in patients aged 80 years and older in most European countries in both the first and the second wave of the pandemic [ 47 ], which is also in line with our single-center findings.…”
Section: Discussionsupporting
confidence: 91%
“…This is in contrast to previous studies from other European countries, which have shown that patients hospitalized during the second wave were relatively younger [ 45 , 46 ]. Despite those age differences among hospitalized patients at different phases of the pandemic, it has been shown that >80% of deaths occurred in patients aged 80 years and older in most European countries in both the first and the second wave of the pandemic [ 47 ], which is also in line with our single-center findings.…”
Section: Discussionsupporting
confidence: 91%
“…As compared to the first wave, second wave infected patients were younger, though had similar clinical presentation but had lower mortality. However, the mean age of died patients was same or older as compared to the first wave [ 45 47 ]. This is interesting and needs to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…The third-year occupational therapy students perceived more stress (50%). We believe this was because they went on placements in old people’s homes, which were very seriously affected by COVID-19 during the pandemic [ 41 ]. The third-year physiotherapy students, and significantly the nursing students, perceived less stress at only 10% and 40% respectively.…”
Section: Discussionmentioning
confidence: 99%